ON ONE BOUNDARY PROBLEM FOR ONE PARABOLIC-HYPERBOLIC EQUATION OF THE THIRD ORDER IN A QUADRANGULAR DOMAIN WITH TWO LINES TYPE CHANGES - M. Mamajonov; Yu.Kharimova (Galaxy International Interdisciplinary Research Journal, 2022)
The study of various problems for equations of the third and higher orders of the parabolic-hyperbolic type began in the 1970s and 1980s .